Prevalence and predictors of out‐of‐field teaching in the first five years - Nixon, Ryan S.; Luft, Julie A.; Ross, Richard J. (Journal of research in science teaching, 2017)
Many new science teachers are assigned to teach subjects in which they have not been prepared, a practice referred to as out-of-field (OOF) teaching. Teaching OOF has been shown to negatively influence instruction and constrain teachers' development. In this study, we explored the extent to which new secondary science teachers were assigned OOF across their first 5 years. Analysis of this longitudinal data set indicated that these assignments were common. While new science teachers were assigned to teach a variety of subjects over their first 5 years of teaching, they were not assigned more or fewer OOF courses over time. Furthermore, results indicated that teachers in certain situations are more likely than others to be assigned to teach OOF. Even with federal legislation in the United States seeking to eliminate OOF teaching, a large portion of new secondary science teachers are assigned to teach science disciplines for which they are inadequately prepared. Based on the findings of this study, it is worth exploring policy avenues that eliminate OOF teaching. Policymakers, administrators, and teacher educators should seek to provide supports, such as science-specific induction programs designed for new teachers who are assigned OOF, and science teacher educators should prepare prospective teachers to teach multiple science disciplines.